Rhetorical genres in «Relação da missão da serra da Ibiapaba», of Father Antônio Vieira - Santos, Fernanda (2022)
«Relação da missão da serra da Ibiapaba» is a text by Father Antônio Vieira from 1660th. After some frustrated missions to the region, Vieira decides to write the report as a way to collect resources for the Ignatians and, above all, obtain a favorable position from the Portuguese Crown. It is intended to analyze the rhetorical preceptives of «Relação» and its belonging to the demonstrative (or ecfrasic), deliberative and judicial genres, from classic authors such as Aristotle, Plato and Quintiliano. If, on the one hand, the text does not shy away from showing the hardness of the obstacles faced by missionaries, on the other hand, Ibiapaba is configured as a locus amoenus, in horaceous terms. The text's descriptive capacity (evidentia) shows a series of historical, geographic and ethnographic elements that allow the understanding of the temporal and spiritual action of the Society of Jesus in Portuguese America, in full Counter-Reform. The mission to Ibiapaba intends to allegorize, narratively, Ignatian conquests in Brazilian lands. More than that, «Relação» is based on the Society of Jesus’s providential theological-political thinking, with the inscription of the future in the events narrated. In addition to the classic authors mentioned above, the article is based on studies on the rhetorical genres of Rodolpho (2014), Santos (2018 and 2019), Guedes (2014), Pernot (2000) and within the scope of the allegorization and providentialism of Society of Jesus, Lima (2009), Hansen (1993 and 2017), Sartorelli (2011) and Luz (2018).